Kyselina listová a prevence rozštěpových vad centrálního nervového systému - Doležálková, E; Unzeitig, V (Ceska gynekologie, 2014)
OBJECTIVE: Overview of neural tube defect in relation to use of folic acid among fertile-age women. DESIGN: Review article. SETTING: Obstetrics and gynecology department OU and FN Ostrava. METHODS AND RESULTS: Neural tube defects (NTDs) are one of the most common birth defects in the Czech Republic. The relation between using of folic acid and decrease of the incidence NTDs was first described in 1965. Fertile-age women are not able to get enough folate from their diet, therefore right timing and proper dosing of folic acid is the object of numerous studies. Many countries started theirs food fortification programs because of the high percentage of unplanned pregnancies and often low compliance. CONCLUSION: The role of folic acid in prevention of NTDs is undeniable. Due to the large number of unplanned pregnancies long-term supplementation is recommended for all fertile-age women. If pregnancy is planned, the suplementation should begin at least one month before pregnancy. In both cases it is necessary to continue until the end of the week of 12. dosage should be individualized according to risk.
Keywords: Dietary Supplements; defekty neurální trubice; Neural Tube Defects; Female; Folic Acid; kyselina listová; Pregnancy; Humans; ženské pohlaví; Prenatal Care; lidé; Vitamin B Complex; vitamin B komplex; těhotenství; potravní doplňky; prenatální péče